2012
DOI: 10.1111/j.1467-8411.2012.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Monetary policy transmission and macroeconomic policy coordination in Pacific island countries

Abstract: During the global financial crisis, central banks in Pacific island countries eased monetary policy to stimulate economic activity. Judging by the ensuing movements in commercial bank interest rates and private sector credit, monetary policy transmission appears to be weak. This is confirmed by an empirical examination of interest rate pass-through and credit growth. Weak credit demand and under-developed financial markets seem to have limited the effectiveness of monetary policy, but the inflexibility of exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Yang, Davies, Wang, Dunn, and Wu (2012) have commented that monetary policy transmission appears to be weak in Pacific Island countries during the global financial crisis. According to them, underdeveloped financial markets and low credit demand have made monetary policy ineffective.…”
Section: The Effectiveness Of Monetary Policy: a Review Of Empirical mentioning
confidence: 99%
“…Yang, Davies, Wang, Dunn, and Wu (2012) have commented that monetary policy transmission appears to be weak in Pacific Island countries during the global financial crisis. According to them, underdeveloped financial markets and low credit demand have made monetary policy ineffective.…”
Section: The Effectiveness Of Monetary Policy: a Review Of Empirical mentioning
confidence: 99%
“…In a more 'business as usual' scenario, Weber (2005) notes, for the case of Cabo Verde, that this regime leads to persistent high-interest rates that detract from domestic investment and economic growth. On the other hand, the lower capital inflows attracted by these kinds of economies allow them to enjoy a certain degree of freedom under a fixed exchange regime (Yang et al, 2012).…”
Section: Monetary Policy On Small Islandsmentioning
confidence: 99%
“…This entails, for instance, that rather than the interest rate, both the money and the exchange rate emerge as the main channel of monetary policy to affect the real economy (Jayaraman and Dahalan, 2008; Ramlogan, 2004). Unsurprisingly, many small islands have historically opted for fixed or managed exchange rate regimes (IMF, 2019; Jayaraman and Choong, 2010; Yang et al, 2012). Rodriguez-Fuentes (2017) goes a step further and argues that, given the aforementioned circumstances, Caribbean islands are ‘incapable’ of conducting their own monetary policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For studies on PICs in general, Yang et al (2012) found that interest rates and private sector credit channels of monetary policy transmission appear to be weak for the region, where weak credit demand and underdeveloped financial markets seem to have limited the effectiveness of monetary policy. Peiris and Ding (2012) showed that PICs are vulnerable to commodity price shocks, which poses challenges for monetary policy, given a high degree of exchange rate pass-through to inflation.…”
Section: Introductionmentioning
confidence: 99%